The Nahdlatul Ulama Model of Thought Renewal as a Foundation for Religious Moderation - Nuril fitria Hidayati; Waqiatul Masruroh (Penerbit Hellow Pustaka, 2025)
This article examines the religious thought espoused by Nahdlatul Ulama (NU), and its central role in laying a solid foundation for religious moderation in Indonesia. Historically and sociologically, NU has successfully transformed Islamic teachings into an inclusive and adaptive social force, through the Ahlussunnah wal Jama'ah (Aswaja) framework, dynamically interpreted as a methodology of thought (manhaj al-fikr). This qualitative research, based on a critical literature review of the works of NU thinkers, demonstrates that the core of renewal lies in the dialectic between the conservation of tradition (maintaining the good old) and contextual innovation (embracing the better new). This model serves as a natural antithesis to extremist narratives, positioning NU as a key anchor for the global discourse on washatiyyah (moderate) Islam.